Resolving Uncertainty About the Intolerance of Uncertainty Scale–12: Application of Modern Psychometric Strategies. Issue 2 (3rd March 2016) - Hale, Willie; Richmond, Miranda; Bennett, Janet; Berzins, Tiffany; Fields, Alexander; Weber, David; Beck, Mark; Osman, Augustine
Abstract: In this study, we evaluated the factor structure, reliability estimates, item parameters, and differential correlates of the short form of the Intolerance of Uncertainty Scale (Carleton, Norton, & Asmundson, 2007 ) in samples of undergraduate women ( n = 387) and men ( n = 276) ranging in age from 18 to 49 years ( M = 20.20, SD = 3.91). This instrument was designed to measure 2 facets of intolerance of uncertainty—prospective anxiety and inhibitory anxiety—although total scores on the measure are often used. A major objective of this study was to determine the degree to which derivation of total versus subscale scores is empirically permissible. Comparison of a bifactor model to a unidimensional model and a 2-factor correlated traits model indicated that the bifactor model exhibited superior fit to the sample data. This model provided evidence of a strong general intolerance of uncertainty factor that was more reliable and accounted for significantly more common variance than either subscale factor. Examination of the item response theory slope parameters revealed negligible bias in the measure's items across genders. Finally, a series of simultaneous regression analyses was conducted to examine differential correlates of the measure's total scale scores for men and women.